PERCEIVED IMPACT OF GRAMMAR COMPETENCE TOWARD THE SPEAKING ABILITY: FOCUSING ON THE ENGLISH LITERATURE STUDENTS OF UNIVERSITAS SAINS ALQUR’AN IN ACADEMIC YEAR 2017/2018 - SAHID SAHID (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
This study aims at exploring the perceived impact of grammar competence among the students of English literature. Participant observation and in-depth interview are conducted to the students of English literature in Universitas Sains Alqur’an in academic year 2017/2018. The data is then comprehensively analyzed using descriptive qualitative method. The result of this study shows that based on the students` perception, the grammar competence really influences the students’ speaking ability. Mostly the students perceived that the goodness of speaking ability depends on the grammar competence. There is only in the certain condition that the student has good speaking ability in less of grammar competence. The students also have different attitudes/ways to develop the speaking ability and grammar competence.